Physical exercise and mitochondrial function: New therapeutic interventions for psychiatric and neurodegenerative disorders - Sun, Lina; Liu, Tianbiao; Liu, Jingqi; Gao, Chong; Zhang, Xiaohui (Frontiers in Neurology, 2022)
Psychiatric and neurodegenerative diseases including major depression disorder (MDD), bipolar disorder and Alzheimer’s disease become growing burdens to society. Deficits of adult hippocampal neurogenesis (AHN) has been widely considered as the main hallmark of psychiatric diseases as well as neurodegeneration. Herein, exploring applicable targets for improving hippocampal neural plasticity could provide the breakthrough for development of new treatments. Emerging evidence indicates the broad functions of mitochondria in regulating cellular behaviors of neural stem cells, neural progenitors, and mature neurons in adulthood, which are considered could offer the multiple neural plasticity to behavioral modulation. Normalizing mitochondrial functions could be a new direction for neural plasticity enhancement. Exercise, the highly encouraged integrative medication in preventing diseases, have been indicated as the effective pathway to improve both mitochondrial functions and AHN. Herein, the relative mechanisms of mitochondria in regulating neurogenesis and its effects in linking the effects of exercise to neurological diseases requires a systematic summary. In this review, we over viewed the relationship between mitochondrial functions and AHN to consider the mitochondria as the potential targets for treating neurological diseases. Moreover, as for one of well-established alternative therapeutic approaches, we summarized the evidence to show the underlying mechanisms of exercise to improve mitochondrial functions and AHN.